Terminalia bellericia (Gaertn.) Roxb. Fruit Extracts Inhibit the Growth of Bacterial Triggers of Selected Autoimmune Inflammatory Diseases and Potentiate the Activity of Conventional Antibiotics - Wang, Kun; Xiao, Mengqi; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: An increase in antibiotic resistance and a corresponding decrease in antimicrobial drug discovery have focused researchers on alternative therapies, including plant-based medicines. However, synergistic combinations of plant extracts with conventional antibiotics may be a far more effective approach in overcoming resistance and potentiating the activity of antibiotics that are otherwise ineffective against resistant bacterial strains. Materials and Methods: The antibacterial activity of Terminalia bellericia fruit extracts was investigated by disc diffusion assays and quantified by liquid dilution and solid phase MIC assays. The extracts were also combined with a range of conventional antibiotics and tested against various microbial triggers of autoimmune diseases. The ΣFIC values obtained from these assays were used to determine the class of combinational effects. Toxicity was evaluated by Artemia nauplii mortality and HDF cytotoxicity assays. Results: Methanolic, aqueous and ethyl acetate T. bellericia fruit extracts had noteworthy growth inhibitory activity against the microbial triggers of several autoimmune inflammatory diseases including P. mirabilis, P. vulgaris, K. pneumoniae, A. baylyi, P. aeruginosa and S. pyogenes. Of further interest, some combinations of the T. bellericia fruit extracts and conventional antibiotics potentiated bacterial growth inhibition compared to the individual components alone. Seven synergistic and seven additive interactions were noted, particularly in combinations containing chloramphenicol as the antibiotic component. Notably, no antagonistic interactions were evident, indicating that all combinations could be used without decreasing the antibacterial activity of the individual components. All extracts were nontoxic in the ALA and HDF assays. Conclusion: Terminalia bellericia fruit extracts have potential as inhibitors of bacterial triggers of selected autoimmune inflammatory diseases. Furthermore, extract components may also potentiate the activity of three antibiotics that are relatively ineffective alone. Isolation and identification of these compounds may be beneficial in drug design against several bacteria, including the microbial triggers of rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis and rheumatic fever.
Keywords: Combretaceae; Synergy; Conventional antimicrobials; Medicinal plants; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Drug combinations.